Generator Revenue Adequacy in the Competitive Electricity Markets: The case of Malaysia - Othman, Nurehan; Hassan, Mohammad Yusri; Hussin, Faridah; Abdullah, Md Pauzi (International Journal of Integrated Engineering, 2014)
Malaysia, like many other developing countries, is reforming its electric supply industry into a more transparent, efficient and competitive environment. The introduction of Independent Power Producers (IPPs) in 1992 was the first step taken to encourage the private investors to participate in the generation sector. The adoption of the single buyer market model in 2001 was a step further to create competition in generation. However, these efforts invite the financial crisis due to IPP generation capacity price obligation and generation surplus as stated in the Power Purchase Agreement (PPA). As the PPA is coming towards the end, the pool market model was initially identified as a possible model to overcome the weaknesses of the single buyer market. However, this model could invite a lot of denials from the power producers if it is not implemented properly. This paper proposes a hybrid market model to satisfy the generator revenue adequacy in Malaysian electricity markets under a competitive environment. A case study of Malaysia’s electricity market system is used to illustrate the proposed market. The result shows that the proposed market model has merit over a pool market model in the context of guaranteed revenue remuneration for each generator. The hybrid model proposed in this paper could effectively be used by ESI in developing countries as a first step of introducing a competition in their electricity market